IMPROVING STUDENT’S READING COMPREHENSION THROUGH SCANNING TECHNIQUE AT THE SECOND GRADE OF THE JUNIOR HIGH SCHOOL - Revaldo Irenius Djuma; Noldy Palengkahu; Maikel B.G Sanger (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2021)
The purpose of the research paper,